PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA PURASARI, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Kusumaningrum, Ria; Suryani, Ermi; Yani, Pitri (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
This community service aims to provide information and education to families about the basic principles of Islamic financial planning. The target subjects of this activity are the residents of Purasari Village, Leuwiliang District, Bogor Regency, West Java Province. The community service program is carried out using a Community-Based Research (CBR) approach, a research-based service method centered on the community. This method involves four stages: establishing a foundation, research planning, data collection and analysis, and action based on findings. The results of this community service indicate an increase in public understanding of the importance of financial planning that aligns with Islamic principles. This initiative has shown that understanding and applying Islamic financial principles are essential to family welfare. The implementation of Islamic financial planning not only enhances financial awareness but also promotes more ethical and responsible financial practices. It is hoped that these efforts will improve the community's quality of life and help them achieve sustainable economic goals.